Histone H3K36 mutations promote sarcomagenesis through altered histone methylation landscape - Lu, Chao (Science, 2016)
Several types of pediatric cancers reportedly contain high frequency missense mutations in histone H3, yet the underlying oncogenic mechanism remains poorly characterized. Here, we report that the H3 lysine 36 to methionine (H3K36M) mutation impairs the differentiation of mesenchymal progenitor cells and generates undifferentiated sarcoma in vivo. H3K36M mutant nucleosomes inhibit the enzymatic activities of several H3K36 methyltransferases. Depleting H3K36 methyltransferases, or expressing an H3K36I mutant that similarly inhibits H3K36 methylation, is sufficient to phenocopy the H3K36M mutation. Following the loss of H3K36 methylation, a genome-wide gain in H3K27 methylation leads to a redistribution of Polycomb Repressive Complex 1 and de-repression of its target genes known to block mesenchymal differentiation. Our findings are mirrored in human undifferentiated sarcomas where novel K36M/I mutations in H3.1 are identified.